2011
DOI: 10.1002/app.34728
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(ε‐caprolactone)/poly(ε‐caprolactone‐co‐lactide) (PCL/PLCL) blend filament by melt spinning

Abstract: Poly(e-caprolactone)/poly(e-caprolactoneco-lactide) (PCL/PLCL) blend filaments with various ratios of PCL and PLCL were prepared by melt spinning. The effect of PLCL content on the physical properties of the blended filament was investigated. The melt spinning of the blend was carried out and the as spun filament was subsequently subjected to drawing and heat setting process. The addition of PLCL caused significant changes in the mechanical properties of the filaments. Crystallinity of blend decreased with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 43 publications
(51 reference statements)
0
40
0
Order By: Relevance
“…Crystallinity degree of PCL was determined using eq. , where Δ H m 0 = 139.5 (J/g) and ω is the polymer weight fraction. χc (%)=true(ΔHmΔHm0ωtrue)×100 …”
Section: Resultsmentioning
confidence: 99%
“…Crystallinity degree of PCL was determined using eq. , where Δ H m 0 = 139.5 (J/g) and ω is the polymer weight fraction. χc (%)=true(ΔHmΔHm0ωtrue)×100 …”
Section: Resultsmentioning
confidence: 99%
“…This is thought to represent the semi‐crystalline lactide in the PLCL. The XRD measurements also confirmed that PLCL67/PLGA33, PLCL33/PLGA67, and PLCL50/PLGA50 show strong peaks at 2 θ = 16.7 and 18.9° and also a weak peak at 22.5°, that is peak of PCL . This supposes that the blending of the two non‐crystalline polymers has helped increase the degree of structural crystallization.…”
Section: Resultsmentioning
confidence: 52%
“…As an example, the crystallinity of the PCL used to synthesize PU 1 was calculated to be 83%. It was obtained by following Equation Crystallinity % = ΔHf × 100ΔHf(crys)where Δ Hf is the melting enthalpy of the sample and Δ Hf (crys) is the melting enthalpy of 100% crystalline PCL and was taken as 139.5 J g −1 .…”
Section: Resultsmentioning
confidence: 99%